TROSO WEAVING FESTIVAL: A CATALYST FOR CULTURAL CO-CREATION - Indaryani, Mamik; Lusianti, Dina; Zuliyati, Zuliyati; Rahmawati, Noor Indah; Krisnanda, Krisnanda; Yusof, Rushami Zien (LPPM Universitas Jambi, 2024)
This research aims to analyze the role of the Troso Weaving Festival in Jepara, Central Java, Indonesia, with formation as cultural value co-creation. Professional organizers and event experience can impact the emergence of a sense of happiness and unforgettable experience, leading to loyal consumers. Continuous consumers feel loyal and willing to volunteer to invite people to follow the Troso Weaving going to Troso Universal Coverage. This research method uses an exploratory approach considering the need to uncover new insights, understand complex relationships, and overcome existing knowledge gaps in co-creation. The respondents in this study were Troso Weaving Festival Visitors of 310 respondents. This study uses the theory of social cognitive approach to form the cultural value of co-creation. The analysis tool used a structural equation model by partial least squares. The research showed that Professional organizers positively affect the event experience. Entertainment, social contact and interaction, exploration of culture, and togetherness as cultural values are influential in experiencing event festival visitors. Event experience has contributed to mediating Professional organizers in cultural values co-creation. This implies that festivals can involve customers in creating co-creation value, which impacts Troso weaving worldwide, thus creating economic growth in Indonesia.